Analysis of laser radiation using the Nonlinear Fourier transform - Srikanth Sugavanam (Nature Portfolio, 2019)
Mathematical approaches for simultaneous characterisation of localized and extended fields in optical signals are not well developed. Here, the authors demonstrate the application of the Nonlinear Fourier transform approach based on the Zakharov-Shabat spectral problem for the analysis of fibre laser radiation.